Latvijas Pagaidu valdības bruņoto spēku Atsevišķā (studentu) rota: darbība 1918.g. decembris-1919.g. marts - Kāposta, Ilze (Latvijas Universitāte, 2014)
Maģistra darba tēma „Latvijas Pagaidu valdības bruņoto spēku Atsevišķā (studentu) rota: darbība 1918. g. decembris-1919. g. marts” aptver laiku no Latvijas neatkarības nodibināšanas un pirmo aizsardzības spēku veidošanās līdz pirmā plašākā Latvijas teritorijas atbrīvošanas uzbrukuma veiksmīgai īstenošanai. Mērķis ir pētīt Atsevišķās (studentu) rotas darbību noteiktajā laika posmā, konstatējot galvenos darbības aspektus un lomu Latvijas Neatkarības kara sākumposmā. Atsevišķā (studentu) rota ir viena no pirmajām Latvijas Pagaidu valdības bruņoto spēku vienībām un ir unikāla militāra vienība Baltijas reģionā. Tās darbību var iedalīt trīs galvenajos posmos: 1) dibināšanās un formēšanās periods Rīgā 2) apsardzības darbība Dienvidkurzemē 3) dalība Lielupes ofensīvā.

The topic of the Master’s thesis, the Separate (student) company of the Armed Forces of Latvian Provisional Goverment: period of action from December 1918 to March 1919, covers the period from the independence of the Republic of Latvia and the establishment of the first armed forces till the realization of the first successful offensive to liberalize of the latvian territories. The aim of the research is the action of the Separate (student) company in the given time period, stating the main aspects of action, and the role in the initial phases of the Latvian Independence war. The Separate (student) company is one of the first units of the Armed Forces of Latvian Provisional Goverment, and it is a unique military unit in the Baltics. The action of the Separate (student) company can be divided into three periods: 1) establishement and formation period in Riga; 2) guarding action in Southern Kurzeme; 3) participation in the Lielupe offensive.
The Separate (student) company of the Armed Forces of Latvian Provisional Goverment: period of action from December 1918 to March 1919
Keywords: Vēsture